Motion Graphics as a Medium of Knowledge Transfer in Creating Awareness Campaign Towards River Pollution in Selangor - Muhammad Aqil Safwan Adnan; Nur Faizah Mohd Pahme; Cindy Robert (Online Journal for TVET Practitioners, 2025)
Situated in Southeast Asia, Malaysia is rich in natural resources including its extensive river systems. The river’s delights serve as a mean for locals to engage in their daily routines. Nevertheless, the contamination of these waterways due to human activities poses significant threats to both human populations and wildlife. Selangor, one of the states in Malaysia, has a significant influence on the sustainability of rivers in the region due to its large population. Numerous initiatives were carried out to enhance public awareness about the importance of maintaining clean waterways. Given the effectiveness of motion graphics as a contemporary marketing tool, integrating it into awareness campaigns could prove beneficial. The aim of this study is to examine the cause and effect of river pollution in Selangor, the cause of motion graphics is not utilised as a knowledge transfer medium and the elements of motion graphics to communicate effectively. The methodology employed in this study is a mixed-method approach, incorporating a preliminary investigation, literature review, questionnaires, and document analysis. The significance of this project lies in its potential to increase public awareness in keeping rivers in Selangor clean through motion graphics.